Ambipolar Discotic Liquid Crystals Built Around Platinum Diimine‐Dithiolene Cores. Issue 22 (22nd March 2019) - Camerel, Franck; Albert, Grégory; Barrière, Frédéric; Lagrost, Corinne; Fourmigué, Marc; Jeannin, Olivier
Abstract: Platinum diimine dithiolene complexes bearing mesogenic groups on one or both ligands have been prepared through an original ligand metathesis reaction to introduce the dithiolene ligand. The neutral diimine ligands, the intermediate platinum dichloride diimine complexes, and the target compounds were characterized by a combination of electronic (electrochemistry, absorption and emission spectroscopy, DFT calculations) and structural (SAXS, DSC) tools. Several novel liquid crystalline platinum diimine‐dithiolene were identified over a large temperature range, and the systems were endowed with ambipolar properties, associated with the high reversibility of both oxidation and reduction processes. Abstract : New liquid crystals : Highly functional mesogens constructed around ambipolar platinum diimine‐dithiolene cores have been isolated through an original ligand metathesis approach (see figure).